Letterer-Siwe’s Disease - Sri S. Nasar; E. M. Dadi Sujoko (Indonesian Pediatric Society, 1974)
The present report concerns a case of Letterer-Siwe's disease which satisfies the clinical and pathological findings of acute non-lipid reticuloendotheliosis. This is the third case reported in our clinic, the former two were reported by Kho et al. (1961) and Iskandar et al. (1966). Two other cases from other clinics were reported by Tangosaputra and Himawan (1970).